МORPHOLOGICAL RESULT OF DENTAL IMPLANTATION IN PATIENTS WITH DIABETES MELLITUS - Achilova Nodira Ganievna (TADQIQOTLAR, 2026)
Abstract Dental implantation is increasingly performed in older populations, who  frequently  present  with  systemic  comorbidities  such as diabetes  mellitus. The present study aimed to identify morphological predictors associated with postoperative complications and implant success in this high-risk cohort. A total of 30 patients aged 40–65 years were examined, including individuals with varying severity of periodontal disease.  Histological  and  immunohistochemical  analyses  of  gingival  tissues  were conducted to assess local immune responses. The findings demonstrate that alterations in  mucosal  immune  homeostasis—particularly  increased  mast  cell  density, macrophage infiltration, and antigen-presenting cell activity—are strongly associated with postoperative complications. Patients with diabetes exhibited significantly higher rates  of  inflammatory  responses  and  delayed  healing.  Morphological  changes  in trabecular bone structure correlated with disease severity and implant prognosis. These results  suggest  that  immunocompetent  cells  within  the  oral  mucosa  may  serve  as reliable biomarkers for predicting implant outcomes. Preoperative immunomodulatory strategies and careful patient selection are critical to improving clinical success rates.